The Role of Mineralization of Mixed Saliva in the Health of the Oral Cavity and the Influence of the Cariousness of the Teeth (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The purpose of our study was to study the peculiarities of the biophysical properties and the mineralizing potential of the oral fluid in children during the period of destructing permanent teeth.Mixed saliva performs a mineralizing function only under the condition of neutral or weakly alkaline pH value when it is oversaturated with calcium and phosphorus ions. Therefore, the physical properties of mixed saliva have a significant impact on the homeostasis of solid teeth tissues. In modern literature, work devoted to the study of the mineralizing potential and biophysical characteristics of saliva in children, contradictory.The obtained data on the violation of the mineralizing composition and biophysical properties of the oral fluid during the period of destructing permanent teeth testifies to the appropriateness of the appointment of these ages of both the ex- and endogenous prevention of the caries of the teeth immediately after their rubberization.